2005
DOI: 10.1080/14733140500510374
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of counselling with older people: Results of a systematic review

Abstract: In 2003 the British Association for Counselling and Psychotherapy (BACP) commissioned a systematic review of the research evidence relating to counselling older people. This paper reports on some of the findings of this review, particularly those which address the effectiveness of counselling with this population. Electronic searches of the research literature spanned 6 databases and were supplemented by hand-searches of reference lists and key journals, along with an extensive search of the ''grey'' literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Some studies have indicated similar results for clients with dementia, while others have not (Finnema et al. 2000, Hill & Brettle 2005, Verkaik et al. 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Some studies have indicated similar results for clients with dementia, while others have not (Finnema et al. 2000, Hill & Brettle 2005, Verkaik et al. 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Usually, it involves recalling and re‐experiencing the life events of older adults. Although psychologists regard reminiscence therapeutically in improving affect and coping skills, the efficacy of this modality is contentious (Hill & Brettle, ; Karimi et al, ; Lin et al, ). However, reminiscence therapy is a treatment being practised in nursing homes or geriatric health facility (Fujiwara et al, ; Tadaka & Kanagawa, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the context in which cognitive-behavioral therapy was used is in question. Cognitive-behavioral therapy has been effectively used to treat older adults who experience a range of life problems such as depression, anxiety (Hill & Brettle, 2005), and insomnia (McCurry, Logsdon, Teri, & Vitiello, 2007). These life problems often pose an immediate threat to older adults' quality of life.…”
Section: Discussionmentioning
confidence: 99%